2017
DOI: 10.1515/hukin-2017-0072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric Training and Beta-Alanine Supplementation on Maximal-Intensity Exercise and Endurance in Female Soccer Players

Abstract: Plyometric training and beta-alanine supplementation are common among soccer players, although its combined use had never been tested. Therefore, a randomized, double-blind, placebo-controlled trial was conducted to compare the effects of a plyometric training program, with or without beta-alanine supplementation, on maximal-intensity and endurance performance in female soccer players during an in-season training period. Athletes (23.7 ± 2.4 years) were assigned to either a plyometric training group receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 37 publications
1
35
1
Order By: Relevance
“…These data are in line with previous studies showing no effect of BA on short-duration repeated sprints in team sports players (21,22). However, previous research in female football players has shown BA supplementation to improve mean power output during repeated 30-s Wingate sprints (30) and induce greater improvements in repeated-sprint tests when combined with plyometric training compared to training alone (11). It is possible that the highly trained nature of our athletes contributed to these results, since meta-analytical data has shown well-trained individuals to achieve smaller performance gains with supplementation than non-trained individuals (17).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These data are in line with previous studies showing no effect of BA on short-duration repeated sprints in team sports players (21,22). However, previous research in female football players has shown BA supplementation to improve mean power output during repeated 30-s Wingate sprints (30) and induce greater improvements in repeated-sprint tests when combined with plyometric training compared to training alone (11). It is possible that the highly trained nature of our athletes contributed to these results, since meta-analytical data has shown well-trained individuals to achieve smaller performance gains with supplementation than non-trained individuals (17).…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that the highly trained nature of our athletes contributed to these results, since meta-analytical data has shown well-trained individuals to achieve smaller performance gains with supplementation than non-trained individuals (17). The aforementioned studies recruited university level (30) and amateur (11) players, while we employed elite youth players. It is also important to again emphasise that the lack of any changes in these tests may similarly be due to the intense nature of the training program, inhibiting any potential adaptations with or without supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous recommendations have also suggested that PJT should be conducted prior to regular (technical-tactical) training sessions (7,14) so that PJT drills are not performed in a fatigued state (26), to maximize neuromuscular responses. Based on this premise, PJT has usually been applied at the beginning of training sessions (34,37,42). However, PJT has also been implemented after regular workouts.…”
Section: Introductionmentioning
confidence: 99%